Universal flame-retardant master batch and preparation method thereof

By using universal flame retardant masterbatches composed of linear polysiloxane and other materials, the problems of insufficient effective content of montmorillonite and limited universality of flame retardant masterbatches in the prior art are solved, and high versatility and high resistance are achieved Preparation of flame retardant materials with combustion efficiency, suitable for a variety of plastic products.

CN119320558APending Publication Date: 2025-01-17ZHEJIANG JAVA SPECIALTY CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411573011.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

When the existing thermoplastic polymer/montmorillonite nanocomposites realize organically modified montmorillonite masterbatches, the effective content and mass ratio are usually less than 60%, which limits the flame retardant efficiency of the material, and the flame retardant masterbatches require Replacement of the thermoplastic carriers according to different thermoplastic carriers leads to limited versatility and flexibility.

Method used

A universal flame retardant masterbatch consisting of linear polysiloxane, silicone resin, organically modified montmorillonite, coupling agent and crosslinking agent is prepared by planetary stirring and twin screw extruder to prepare thermoplastic-free The high content of the carrier is flame retardant masterbatch, and the flame retardant performance is improved by using polysiloxane crosslinkers.

Benefits of technology

It realizes the high versatility and high flame retardant efficiency of flame retardant masterbatches, and can be widely used in various plastic products without changing the carrier, which significantly improves the flame retardant performance of the material, reduces the generation of smoke and toxic gases, and improves the Product safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a universal flame-retardant master batch. The universal flame-retardant master batch comprises a material A, a material B, a material C and a material D, wherein the material A comprises linear polysiloxane, silicon resin, organic modified montmorillonite, a coupling agent and a cross-linking agent; the material B comprises white carbon black and a catalyst. The invention also provides a preparation method of the universal flame-retardant master batch. The flame-retardant master batch has relatively high flame-retardant efficiency, does not contain a thermoplastic carrier, and is high in universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of polymer materials, and more specifically, relates to a universal flame retardant masterbatch and a preparation method thereof. Background Art

[0002] Thermoplastic polymer / montmorillonite nanocomposites exhibit excellent mechanical, thermal, flame retardant and barrier properties due to their fusion at the nano level. Such materials have broad application prospects in many fields such as electronics, automotive industry, construction, aerospace, wires and cables, household appliances, nanofibers, etc. However, the existing preparation methods have significant limitations in achieving organic modified montmorillonite masterbatch. Specifically, when organic modified montmorillonite masterbatch is prepared using thermoplastic plastic as a carrier, the effective content mass ratio of the organic modifier montmorillonite can usually only reach less than 60%, which seriously limits the flame retardant efficiency of the material.

[0003] In addition, when existing flame retardant masterbatches are used as additives in different plastics, different thermoplastic plastic carriers often need to be replaced. This method of relying on specific carriers greatly limits the versatility and flexibility of flame retardant masterbatches. This limitation not only increases the preparation cost of the material, but also limits its application range in different plastic processing processes. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a universal flame retardant masterbatch and a preparation method thereof. The flame retardant masterbatch has high flame retardant efficiency, does not contain a thermoplastic carrier, and has strong versatility.

[0005] In order to better solve the above problems, the present invention adopts the following technical solutions:

[0006] A universal flame retardant masterbatch, comprising the following components:

[0007] Material A: linear polysiloxane, silicone resin, organic modified montmorillonite, coupling agent, crosslinking agent;

[0008] Material B: white carbon black, catalyst;

[0009] Wherein, the linear polysiloxane has the following structural formula:

[0010]

[0011] Among them, m=100-5000; n=0-20; R1 is one of methyl, vinyl, and hydroxyl; R2 is one or more of methyl, vinyl, trifluoropropyl, phenyl, C6-C20 aromatic group, and C2-C30 alkyl group.

[0012] As a preferred technical solution, the linear polysiloxane has a molecular weight of 10,000-400,000.

[0013] As a preferred technical solution, the silicone resin is one or more of methyl silicone resin, vinyl silicone resin, and phenyl silicone resin.

[0014] As a preferred technical solution, the organic matter of the organic modified montmorillonite is one or more of octadecyl ammonium halide, hexadecyl ammonium halide or dodecyl ammonium halide.

[0015] As a preferred technical solution, the crosslinking agent includes one or a combination of methyl orthosilicate, ethyl orthosilicate, methyltrimethoxysilane, ethyltrimethoxysilane, vinyltrimethoxysilane, propyltrimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, vinyltriethoxysilane, propyltriethoxysilane, phenyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, and hydrogenated silicone oil.

[0016] As a preferred technical solution, the catalyst is one of an organic tin catalyst and a platinum catalyst; the organic tin catalyst includes any one or more of dibutyltin dilaurate, dibutyltin diacetate or stannous octoate; the platinum catalyst includes an isopropanol solution of chloroplatinic acid or a vinyl platinum complex.

[0017] In order to better solve the above technical problems, the present invention also discloses the following technical solutions:

[0018] A method for preparing a universal flame retardant masterbatch, used for preparing the universal flame retardant masterbatch as described in any one of the above, comprising:

[0019] (1) heating and stirring 10-43 parts of linear polysiloxane, 5-10 parts of silicone resin, 50-70 parts of organic modified montmorillonite, and 1-3 parts of coupling agent in a planetary mixer for a certain period of time to obtain semi-exfoliated nanoclay; after cooling, adding 1-7 parts of cross-linking agent, and mixing thoroughly to obtain material A;

[0020] (2) adding white carbon black and a catalyst into a high-speed mixer for treatment to obtain a white carbon black powder loaded with a catalyst as material B;

[0021] (3) Material A is metered into the feed port through the main feed port and material B is metered into the feed port through the side feed port. The feed ports are then cross-linked underwater by a twin-screw extruder and extruded into pellets to obtain a general-purpose high-content flame-retardant masterbatch.

[0022] As a preferred technical solution, in step (1), the temperature of the heating and stirring is 60-150°C, and the stirring time is 1-12h; the temperature of the cooling and adding the cross-linking agent is 0-50°C after cooling, and the stirring time is 5-60min.

[0023] As a preferred technical solution, in step (2), the mass ratio of white carbon black to catalyst is 2:1-50:1.

[0024] As a preferred technical solution, in step (3), the mass ratio of material B to material A is 2-10:1.

[0025] The beneficial effects of the present invention are as follows: the flame retardant masterbatch of the present invention does not contain a thermoplastic carrier, but uses a polysiloxane cross-linked material as a substitute. This design eliminates the dependence on the melting temperature of thermoplastics, so that the scope of use of the flame retardant masterbatch is no longer limited to a specific type of thermoplastic material. Since it is not limited by the type of thermoplastic material, the flame retardant masterbatch of the present invention has extremely high versatility and can be widely used in the production process of various plastic products. There is no need to replace the carrier according to different thermoplastics, which greatly simplifies the production process and reduces costs. In the flame retardant masterbatch of the present invention, the linear polysiloxane itself has good flame retardant properties, so the flame retardant content in the masterbatch reaches 100%, which means that without sacrificing other properties, the flame retardant efficiency of the material can be significantly improved. When encountering a fire source, the plastic product using the flame retardant masterbatch of the present invention can more effectively prevent the spread of flames, reduce the generation of smoke and toxic gases, and thus improve the safety of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The XRD patterns of the flame retardant masterbatch 2 in Example 2 and the flame retardant masterbatch 6 in Comparative Example 1;

[0027] Figure 2 The TGA spectra of the flame retardant masterbatch 2 in Example 2 and the flame retardant masterbatch 6 in Comparative Example 1; DETAILED DESCRIPTION

[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in combination with specific descriptions and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] In order to overcome the shortcomings of the prior art, the present invention provides a universal flame retardant masterbatch and a preparation method thereof, aiming to increase the addition amount of organic modified montmorillonite, thereby improving the flame retardant efficiency of the material, and enabling the flame retardant masterbatch to be widely used in different thermoplastics without replacing the carrier, thereby solving the limitations of the prior art.

[0030] The technical solution of the present application includes: a universal flame retardant masterbatch, including the following components:

[0031] Material A: linear polysiloxane, silicone resin, organic modified montmorillonite, coupling agent, crosslinking agent;

[0032] Material B: white carbon black, catalyst;

[0033] Wherein, the linear polysiloxane has the following structural formula:

[0034]

[0035] Among them, m=100-5000; n=0-20; R1 is one of methyl, vinyl, and hydroxyl; R2 is one or more of methyl, vinyl, trifluoropropyl, phenyl, C6-C20 aromatic group, and C2-C30 alkyl group.

[0036] Specifically, in one embodiment, the molecular weight of the linear polysiloxane is 10,000-400,000, preferably 10,000-200,000, more preferably 10,000-100,000.

[0037] In one embodiment, the silicone resin is one or more of methyl silicone resin, vinyl silicone resin, and phenyl silicone resin.

[0038] In one embodiment, the organic matter of the organic modified montmorillonite is one or more of octadecyl ammonium halide, hexadecyl ammonium halide or dodecyl ammonium halide, preferably octadecyl ammonium halide, more preferably dioctadecyl ammonium halide.

[0039] In one embodiment, the coupling agent is one or more of a silane coupling agent and a titanate coupling agent, preferably a silane coupling agent.

[0040] In one embodiment, the crosslinking agent includes one or a combination of methyl orthosilicate, ethyl orthosilicate, methyltrimethoxysilane, ethyltrimethoxysilane, vinyltrimethoxysilane, propyltrimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, vinyltriethoxysilane, propyltriethoxysilane, phenyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, and hydrogenated silicone oil.

[0041] In one embodiment, the catalyst is one of an organic tin catalyst and a platinum catalyst; wherein the organic tin catalyst includes any one or more of dibutyltin dilaurate, dibutyltin diacetate or stannous octoate; and the platinum catalyst includes an isopropanol solution of chloroplatinic acid or a vinyl platinum complex.

[0042] In one embodiment, the specific surface area of ​​the white carbon black is 50-380 m 2 / g.

[0043] In order to better solve the above technical problems, the present invention also discloses the following technical solutions:

[0044] A method for preparing a universal flame retardant masterbatch, used for preparing the universal flame retardant masterbatch as described in any one of the above, comprising:

[0045] (1) heating and stirring 10-43 parts of linear polysiloxane, 5-10 parts of silicone resin, 50-70 parts of organic modified montmorillonite, and 1-3 parts of coupling agent in a planetary mixer for a certain period of time to obtain semi-exfoliated nanoclay; after cooling, adding 1-7 parts of cross-linking agent, and mixing thoroughly to obtain material A;

[0046] (2) adding white carbon black and a catalyst into a high-speed mixer for treatment to obtain a white carbon black powder loaded with a catalyst as material B;

[0047] (3) Material A is metered into the feed port through the main feed port and material B is metered into the feed port through the side feed port. The feed ports are then cross-linked underwater by a twin-screw extruder and extruded into pellets to obtain a general-purpose high-content flame-retardant masterbatch.

[0048] In one embodiment, in step (1), the temperature of the heating and stirring is 60-150°C, preferably 80-120°C; the stirring time is 1-12h, preferably 3-9h, more preferably 4-6h. The temperature of the cooling and adding the crosslinking agent is 0-50°C, preferably 10-40°C, more preferably 20-30°C after cooling. The stirring time is 5-60min, more preferably 10-20min.

[0049] In one embodiment, in step (2), the mass ratio of white carbon black to catalyst is 2:1-50:1.

[0050] In one embodiment, in step (3), the mass ratio of material B to material A is 2-10:1.

[0051] In one embodiment, in step (3), the extrusion temperature during extrusion granulation is room temperature, the speed is <300 rpm, and the water temperature is >40°C, preferably >70°C.

[0052] In the technical solution of the present application, linear polysiloxane, silicone resin, coupling agent, and organic modified montmorillonite are heated and stirred in a planetary mixer, so that the polysiloxane molecules enter the modified montmorillonite interlayer to obtain semi-exfoliated nanoclay; after cooling, a crosslinking agent is added, and after sufficient mixing, the mixture is used as material A. White carbon black and a catalyst are added to a high-speed mixer for processing to obtain a catalyst-loaded white carbon black powder, which is used as material B. Material A is metered into the main feed port, and material B is metered into the side feed port, and then extruded and granulated by a twin-screw extruder, and finally crosslinked in warm water to obtain a general-purpose high-content flame retardant masterbatch.

[0053] The flame retardant masterbatch of the present invention does not contain a thermoplastic carrier, but uses a polysiloxane crosslinked material as a substitute. This design eliminates the dependence on the melting temperature of thermoplastics, so that the scope of use of the flame retardant masterbatch is no longer limited to a specific type of thermoplastic material. Since it is not limited by the type of thermoplastic material, the flame retardant masterbatch of the present invention has extremely high versatility and can be widely used in the production process of various plastic products. There is no need to replace the carrier according to different thermoplastics, which greatly simplifies the production process and reduces costs. In the flame retardant masterbatch of the present invention, linear polysiloxane itself has good flame retardant properties, so the flame retardant content in the masterbatch reaches 100%, which means that without sacrificing other properties, the flame retardant efficiency of the material can be significantly improved. When encountering a fire source, the plastic product using the flame retardant masterbatch of the present invention can more effectively prevent the spread of flames and reduce the generation of smoke and toxic gases, thereby improving the safety of the product.

[0054] The technical solution of the present application is further described below in conjunction with the embodiments:

[0055] Unless otherwise specified, the raw materials in the following examples and comparative examples were purchased from commercial sources.

[0056] Example 1

[0057] (1) In parts by weight, 10 parts of α,ω dihydroxy polydimethylsiloxane (molecular weight 1w), 70 parts of dodecyl ammonium bromide modified montmorillonite, 10 parts of methyl silicone resin, and 3 parts of aminotriethoxysilane were heated to 60° C. and stirred for 9 hours in a planetary mixer to obtain semi-exfoliated nanoclay; the temperature was lowered to 40° C., 7 parts of ethyl orthosilicate were added, and the mixture was fully mixed for 60 minutes to obtain material A1;

[0058] (2) By weight, 2 parts of white carbon black (specific surface area: 380 m2 / g) and 1 part of catalyst dibutyltin dilaurate were added into a high-speed mixer for treatment to obtain a powder, which was used as material B1;

[0059] (3) By weight, 100 parts of A1 material and 1 part of B1 material were metered into the main feed port and fed into the side feed port, and then crosslinked underwater (60° C.) by a twin-screw extruder (speed 100 rpm) and pelletized to obtain a general-purpose high-content flame retardant masterbatch 1.

[0060] Example 2

[0061] (1) In parts by weight, 39 parts of α,ω dihydroxy polydimethylsiloxane (molecular weight 10w), 5 parts of vinyl silicone resin, 50 parts of montmorillonite modified with octadecyl ammonium chloride, and 1 part of vinyl triethoxysilane were heated to 80°C in a planetary mixer and stirred for 6 hours to obtain semi-exfoliated nanoclay; the temperature was lowered to 30°C, 5 parts of phenyl triethoxysilane were added, and the mixture was fully mixed for 30 minutes to obtain material A2;

[0062] (2) Add 5 parts by weight of white carbon black (specific surface area: 300 m2 / g) and 1 part of catalyst dibutyltin diacetate into a high-speed mixer for treatment to obtain a powder, which is used as material B2;

[0063] (3) In parts by weight, 100 parts of A2 material and 3 parts of B2 material were metered into the mixture through the main feeding port and the mixture was then cross-linked underwater (70° C.) by a twin-screw extruder (speed 200 rpm) and pelletized to obtain a general-purpose high-content flame-retardant masterbatch 2.

[0064] Example 3

[0065] (1) In parts by weight, 26 parts of methyl-terminated polydimethylvinylsiloxane (molecular weight 6w), 60 parts of dodecyl ammonium bromide-modified montmorillonite, 8 parts of phenyl silicone resin, and 2 parts of titanate coupling agent were heated to 90° C. and stirred for 4 hours in a planetary mixer to obtain semi-exfoliated nanoclay; the temperature was lowered to 20° C., 4 parts of octyltriethoxysilane were added, and the mixture was fully mixed for 20 minutes to obtain material A3;

[0066] (2) By weight, 30 parts of white carbon black (specific surface area: 200 m2 / g) and 1 part of a catalyst vinyl platinum complex were added into a high-speed mixer for treatment to obtain a powder, which was used as material B3;

[0067] (3) In parts by weight, 100 parts of A3 material and 7 parts of B3 material were metered into the mixture through the main feeding port and the mixture was then cross-linked underwater (90° C.) by a twin-screw extruder (speed 300 rpm) and pelletized to obtain a general-purpose high-content flame-retardant masterbatch 3.

[0068] Example 4

[0069] 1) In parts by weight, 28 parts of vinyl-terminated polydimethyltrifluoropropylsiloxane (molecular weight 5w), 2 parts of methyl silicone resin, 4 parts of phenyl silicone resin, 60 parts of hexadecyl ammonium chloride-modified montmorillonite, and 3 parts of trifluoropropyltrimethoxysilane are heated to 100° C. and stirred for 3 hours in a planetary mixer to obtain semi-exfoliated nanoclay; the mixture is cooled to 10° C., 3 parts of vinyltriethoxysilane are added, and the mixture is fully mixed for 10 minutes to obtain material A4;

[0070] (2) By weight, 40 parts of white carbon black (specific surface area: 100 m2 / g) and 1 part of a catalyst chloroplatinic acid isopropanol solution were added into a high-speed mixer for treatment to obtain a powder, which was used as material B4;

[0071] (3) In parts by weight, 100 parts of A4 material and 8 parts of B4 material were metered into the mixture through the main feeding port and the mixture was then cross-linked underwater (90° C.) by a twin-screw extruder (speed 200 rpm) and pelletized to obtain a general-purpose high-content flame-retardant masterbatch 4.

[0072] Example 5

[0073] 1) In parts by weight, 24 parts of vinyl-terminated polydimethylphenylsiloxane (molecular weight 3w), 8 parts of methyl silicone resin, 60 parts of dioctadecyl ammonium chloride-modified montmorillonite, and 3 parts of titanate coupling agent are heated to 120° C. in a planetary mixer and stirred for 1 hour to obtain semi-exfoliated nanoclay; the mixture is cooled to 0° C., 5 parts of hydrogenated silicone oil are added, and the mixture is fully mixed for 5 minutes to obtain material A5;

[0074] (2) By weight, 50 parts of white carbon black (specific surface area: 50 m2 / g) and 1 part of a catalyst vinyl platinum complex were added into a high-speed mixer for treatment to obtain a powder, which was used as material B5;

[0075] (3) In parts by weight, 100 parts of A5 material and 10 parts of B5 material were metered into the feed port through the main feed port and the feed port through the side feed port, and then crosslinked underwater (90° C.) by a twin-screw extruder (speed 100 rpm) and pelletized to obtain a general-purpose high-content flame retardant masterbatch 5.

[0076] Comparative Example 1

[0077] In parts by weight, 50 parts of polyethylene and 50 parts of montmorillonite modified by octadecyl ammonium chloride were fed through the main feeding port and granulated underwater by a twin-screw extruder (speed 300 rpm) to obtain flame retardant masterbatch 6.

[0078] Comparative Example 2

[0079] In parts by weight, 40 parts of polyethylene and 60 parts of dodecyl ammonium bromide modified montmorillonite were fed through the main feeding port and granulated underwater by a twin-screw extruder (speed 300 rpm) to obtain flame retardant masterbatch 7.

[0080] Comparative Example 3

[0081] In parts by weight, 40 parts of polyethylene and 60 parts of cetyl ammonium chloride-modified montmorillonite were fed through a main feed port and granulated underwater by a twin-screw extruder (speed 300 rpm) to obtain a flame retardant masterbatch 8.

[0082] Comparative Example 4

[0083] In parts by weight, 40 parts of polyethylene and 60 parts of dioctadecyl ammonium chloride modified montmorillonite were fed through the main feeding port and granulated underwater by a twin-screw extruder (speed 300 rpm) to obtain a flame retardant masterbatch 9.

[0084] The flame retardant masterbatch 2-9 obtained above was subjected to a thermogravimetric analysis test; it was added to the low-smoke halogen-free cable material at an addition amount of 5%, and the performance of the prepared fire-resistant cable material 1-8 was tested. The test results are shown in Table 1.

[0085] Specific test method: The vertical combustion test is conducted using ANST / UL94-1985; the test conditions for high-temperature residual volume are: nitrogen atmosphere, room temperature -800°C.

[0086] Table 1

[0087] High temperature residual content, % Flame retardant masterbatch 2 35.2 Flame retardant masterbatch 3 38.9 Flame retardant masterbatch 4 40.4 Flame retardant masterbatch 5 42.3 Flame retardant masterbatch 6 22.6 Flame retardant masterbatch 7 26.9 Flame retardant masterbatch 8 26.4 Flame retardant masterbatch 9 25.9

[0088] Table 2

[0089]

[0090] It can be seen from the test results in Table 1 that the flame retardant masterbatch prepared in the present invention has a significantly increased high-temperature residue when the content of organic modified montmorillonite is the same. This is because the cross-linked polysiloxane and silicone resin can also be used as flame retardants themselves and have a large high-temperature residue.

[0091] It can be seen from the test results in Table 2 that, compared with the flame retardant masterbatch obtained in Comparative Examples 1-4, the flame retardant masterbatch prepared by the present invention can effectively improve the mechanical properties of the fire-resistant cable when used in the preparation of the fire-resistant cable, especially the elongation at break is better, and the flame retardant effect is excellent.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A universal flame retardant masterbatch, characterized in that: Includes the following components: Material A: linear polysiloxane silicone resin, organic modified montmorillonite, coupling agent, crosslinking agent; Material B: white carbon black, catalyst; Wherein, the linear polysiloxane has the following structural formula: Among them, m=100-5000; n=0-20; R1 is one of methyl, vinyl, and hydroxyl; R2 is one or more of methyl, vinyl, trifluoropropyl, phenyl, C6-C20 aromatic group, and C2-C30 alkyl group.

2. The universal flame retardant masterbatch according to claim 1, characterized in that: The linear polysiloxane has a molecular weight of 10,000 to 400,000.

3. The universal flame retardant masterbatch according to claim 1, characterized in that: The silicone resin is one or more of methyl silicone resin, vinyl silicone resin and phenyl silicone resin.

4. The universal flame retardant masterbatch according to claim 1, characterized in that: The organic matter of the organic modified montmorillonite is one or more of octadecyl ammonium halide, hexadecyl ammonium halide or dodecyl ammonium halide.

5. The universal flame retardant masterbatch according to claim 1, characterized in that: The crosslinking agent includes one or a combination of methyl orthosilicate, ethyl orthosilicate, methyltrimethoxysilane, ethyltrimethoxysilane, vinyltrimethoxysilane, propyltrimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, vinyltriethoxysilane, propyltriethoxysilane, phenyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, and hydrogenated silicone oil.

6. The universal flame retardant masterbatch according to claim 1, characterized in that: The catalyst is one of an organic tin catalyst and a platinum catalyst; the organic tin catalyst includes any one or more of dibutyltin dilaurate, dibutyltin diacetate or stannous octoate; the platinum catalyst includes an isopropanol solution of chloroplatinic acid or a vinyl platinum complex.

7. A method for preparing a universal flame retardant masterbatch, used for preparing the universal flame retardant masterbatch according to any one of claims 1 to 6, characterized in that: include: (1) heating and stirring 10-43 parts of linear polysiloxane, 5-10 parts of silicone resin, 50-70 parts of organic modified montmorillonite, and 1-3 parts of coupling agent in a planetary mixer for a certain period of time to obtain semi-exfoliated nanoclay; after cooling, adding 1-7 parts of cross-linking agent, and mixing thoroughly to obtain material A; (2) adding white carbon black and a catalyst into a high-speed mixer for treatment to obtain a white carbon black powder loaded with a catalyst as material B; (3) Material A is metered into the feed port through the main feed port and material B is metered into the feed port through the side feed port. The material is then cross-linked underwater by a twin-screw extruder and extruded into pellets to obtain a general-purpose high-content flame-retardant masterbatch.

8. The method for preparing a universal high-concentration flame retardant masterbatch according to claim 7, characterized in that: In step (1), the temperature of the heating and stirring is 60-150° C., and the stirring time is 1-12 hours; the temperature of the cooling and the addition of the cross-linking agent is 0-50° C. after cooling, and the stirring time is 5-60 minutes.

9. The method for preparing a universal high-concentration flame retardant masterbatch according to claim 7, characterized in that: In step (2), the mass ratio of white carbon black to catalyst is 2:1-50:

1.

10. The method for preparing a universal high-concentration flame retardant masterbatch according to claim 7, characterized in that: In step (3), the mass ratio of material B to material A is 2-10:1.